Peran QRIS dalam Digitalisasi Sistem Pembayaran UMKM: Analisis Manfaat dan Hambatan - Atanasius Basilika Chrisna Dellon; Aisyah Lovayudina Retang; Anna Triwijayati; Catharina Aprilia Hellyani (Jurnal Manajemen Bisnis Era Digital, 2026)
This study examines the role of QRIS as a non-cash payment system in supporting the digitalization of micro, small, and medium enterprises (MSMEs) in Indonesia. The rapid growth of digital transactions has encouraged MSMEs to adopt more efficient, practical, and secure payment systems. This study aims to integrate the benefits and barriers of QRIS, map its position in the MSME digitalization process, and develop a conceptual framework for future research. A descriptive qualitative approach with a literature study design was employed, utilizing relevant academic sources related to QRIS, MSMEs, digital payments, and user behavior. Data were analyzed using content analysis by comparing, interpreting, and synthesizing findings from selected literature. The results indicate that QRIS contributes to simplifying transactions, improving operational efficiency, reducing cash dependency, and supporting MSMEs’ adaptation to digital payment trends. However, its implementation remains constrained by factors such as digital literacy, user readiness, trust, and infrastructural limitations. The study also highlights that QRIS adoption is influenced not only by technological advantages but also by perceived value and user trust. Therefore, QRIS can be positioned as a strategic instrument in accelerating the digital transformation of MSME payment systems. The findings imply the need for further empirical research to examine the direct impact of QRIS adoption on MSME performance and sustainability.